Design e usabilidade: interação, satisfação e afetividade em objetos de aprendizagem - Ferraresso, Henrique Luiz Perroni [UNESP] (2014)
With regard to digital native students, you bet on the use of technology in the classroom as a motivating factor and, if properly used, a satisfactory tool to support teaching in the transmission and construction of knowledge. However, many of the digital educational materials developed to date require a more detailed and functional for better production and development analysis. Many of the analyzes conducted to understand the quality of an educational software focus only in the issue of usability of the system, and for educational material is not enough t evaluate the usability of the system, but also his ability to convery pedagogical content sothe user to obtain satisfaction in this interaction. In learning situations Design acts as a line of inquiry, preferably inserted in the academic field. it basic principle is to improve the process os knowledge construction. Accordingly, each design solution is the search for balance between interests and needs of users as well as companies and educational bodies turned to production of instructional materials and educational materials and software. The present study aimed to explore the role of design process of learning, through the concept of Affection found on Bloom's Taxonomy. Such a connection was possible, by understanding that the design directly influence the factor of Affection and this is present in the learning process of an individual. From the results obtained, it was possible to find a corresponding interaction between data analysis and usability of affection, present the evaluation of learning criteria of Bloom, thus indicating a relationship between these factors and possible interdependence has not seen more scientific deepening. Thus, the survey show that it is possible to perceive a connection between the factors: design usability, and affectivity learning and that the user perceives them with some connection since they considered an acceptable product when the presence of...